Safety of women commuters : a case study in Penang / Rohana Sham - Sham, Rohana (2007)
Women who commute to work using current bus services tend to rate a higher level of unsafe or fear when they indicate a high level of dissatisfaction towards the current service and infrastructure provision. Added with different time of travelling and different age group of women commuters who depend on different type of bus services (stage bus and work bus) to commute to work, it is also of interest to look at these factors and the effect on the level of safety indication. This study compares the level of safety indication for women traveling in three different urban areas in Penang Island namely Pulau Tikus, Ayer Itam and Jelutong with different transport service and infrastructure provisions. The aim of the study is to gauge a better understanding of the relationships between the satisfaction of the existing transport service characteristics and women travel pattern towards the level of safety indication while travelling at different satisfactory level of infrastructure provision. A key question in this study is whether bus service characteristics, and women travel pattern playa role as a factor affecting the level of safety indication when controlling for the infrastructure provision in their respective areas. Finding from the correlation and partial correlation analysis indicated that different types of bus service possess different service characteristics that affect their level of safety. However for women travel pattern characteristics like 'time' and 'age' of women traveling, both of the factors had been identified as significant factors that affect level of safety even after controlling for the infrastructure provision for both the stage bus and work bus users. Further comparison on the service, infrastructure and level of safety for different location studied were being carried out through one-way Analysis of Variance. A passenger survey underpin the methodology employed, where the sample came from the three major areas to identify the real factors contributing towards their fear level. The data collected were analyzed by means of a statistical package, SPSS. The study concludes with a discussion of results and suggestions for future research. The study is a contribution to a relatively urban area scenario in the geography of crime and public transport supply with women as a dominant traveller.